The Phonics Playbook : How to Differentiate Instruction so Students Succeed - Ryan, Alison, (Literacy specialist) (Hoboken, New Jersey : John Wiley & Sons, 2024)
"Differentiation has been shown to improve student outcomes in phonics learning, and many teachers are at a loss concerning how to incorporate differentiation in their everyday classrooms. When students' phonics knowledge grows, their reading fluency increases. And when reading fluency improves, children can devote more of their working memories to comprehension, which is the ultimate goal of reading. Focusing on differentiation in phonics instruction is worth teachers' time and attention"--
Includes index.
Keywords: Reading -- Phonetic method -- Study and teaching; Academic achievement; Group work in education